Age-Related Eyelid Diseases - Sevimli, Neslihan; Karadag, Remzi; Cakici, Ozgur; Bayramlar Hüseyin (Journal of Ocular Diseases and Therapeutics, 2015)
Although aging is natural and acceptable process by most people, it has become a major problem with increased life expectancy and socio-cultural levels. The eyelid protects eyes from dryness, environmental exposure and trauma. It is important that the eyelid is to be robust and in the proper position for eye health.